Analysis of the composition, structure, diversity and uses of vegetation in a landscape of the Tehuacán-Cuicatlán Biosphere Reserve, Mexico - Zavaleta, Arturo; Mandujano, Salvador; López-Téllez, Concepción (Instituto de Ecología, A.C., 2023)
Tropical dry forests maintain a high diversity and endemic flora and fauna but are among the most threatened ecosystems in the world. In the present study we analyzed the composition, structure, diversity and traditional uses of the plants in a locality of the Tehuacán-Cuicatlán Biosphere Reserve, Oaxaca, Mexico. The vegetation in the study landscape is representative of the semi-arid areas composed by tropical dry forest, scrub, and agricultural areas. During the rainy season of 2018, 30 sampling sites were sampled. A total of 71 species belonging to 24 botanical families were identified. The best represented Families were Cactaceae, Euphorbiaceae and Leguminocea; while the species were Neobuxbaumia tetetzo, Bursera fagaroides, Opuntia pilifera, Myrtillocactus geometrizans and Amphipterygium adstringens. The composition of species varied among the different landscape units, being the unit with agricultural presence the one that had the least diversity of species. Based on interviews, a total of 54 species of plants with traditional uses in the locality were determined. The results of the present study suggest that under an adequate management scheme and conservation plans such as those practiced in this site, the representative composition and plant diversity of this reserve can be maintained.